Efforts to Combat Sexual Violence Against Women and Children in Makassar City (Qawanin Jurnal Ilmu Hukum, 2025)
This article reveals efforts to overcome sexual violence against women and children in the city of Makassar and the factors that influence efforts to overcome sexual violence against women and children in the city of Makassar. The empirical research method was chosen to describe the legal reality in the community in an area that became the research location. The results of this study indicate that efforts to overcome sexual violence against women and children in the city of Makassar are still not maximized. Efforts to overcome sexual violence against women and children in Makassar City carried out by the PPA Unit of the Sul-Sel Regional Police are in the form of pre-emtif, preventive, and repressive efforts. The factors that influence countermeasures carried out by investigators are external and internal factors which include the lack of quantity and quality of investigators, lack of facilities and infrastructure, lack of operational costs, lack of evidence, and lack of community participation.Abstrak:Artikel ini mengungkapkan upaya penanggulangan kekerasan seksual terhadap perempuan dan anak di kota makassar serta faktor-faktor yang memengaruhi upaya penanggulangan kekerasan seksual terhadap perempuan dan anak di kota makassar. Metode penelitian empiris dipilih untuk mendeskripsikan kenyataan hukum pada masyarakat pada sebuah wilayah yang menjadi lokasi penelitian. Hasil penelitian ini menunjukkan bahwa upaya penanggulangan kekerasan seksual terhadap perempuan dan anak di kota makassar masih kurang maksimal. Upaya penanggulangan kekerasan seksual terhadap perempuan dan anak di Kota makassar yang dilakukan oleh Unit Pelayanan Perempuan dan Anak Kepolisian Daerah Sulawesi Selatan yaitu berupa upaya pre-emtif, preventif, dan upaya represif. Adapun faktor-faktor yang mempengaruhi upaya penanggulangan yang dilakukan oleh penyidik berupa faktor eksternal dan internal yang meliputi kurangnya kuantitas dan kuaitas penyidik, kurangnya sarana dan prasarana, kurangnya biaya operasional, kurangnya alat bukti, serta kurangnya partisipasi masyarakat.